The Women’s Leadership: Orientation from a Legal and Islamic Sharia Perspective - Fatmawati; Rahma Amir; Rahmawati; Firman Muhammad Arif; Muhammad Shuhufi (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
Women’s leadership in the political dimension is an interesting study because even though Indonesia has substantially regulated women’s leadership, in practice women’s leadership has not been implemented optimally. This research aims to answer two legal issues, namely the legal political orientation related to women’s leadership in politics in Indonesia, as well as the perspective of Islamic law related to women’s leadership in politics in Indonesia. This research is normative legal research with a conceptual and statutory approach. The research results confirm that the problems regarding legal politics for women to hold political positions are more related to aspects of legal culture and collective understanding of society. This emphasizes that legal politics related to the role and orientation of women’s leadership in the world of politics must receive optimal understanding and awareness in society so that women get more portions and roles to occupy political positions in proportion to men’s political leadership. Apart from that, from the perspective of Islamic Sharia regarding women’s leadership in politics in Indonesia, there is actually no definite prohibition (qath’i) that prohibits women from becoming political leaders. Therefore, referring to the Maqashid Asy-Syariah aspect, it refers to the development of time and culture, especially when women also have the same opportunities to receive education so that they have the same potential to become political leaders as men.